2013
DOI: 10.1093/jxb/ert052
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ABA synthesis and metabolism genes under different irrigation strategies and atmospheric VPDs is associated with stomatal conductance in grapevine (Vitis vinifera L. cv Cabernet Sauvignon)

Abstract: The influence of different levels of irrigation and of variation in atmospheric vapour pressure deficit (VPD) on the synthesis, metabolism, and transport of abscisic acid (ABA) and the effects on stomatal conductance were examined in field-grown Cabernet Sauvignon grapevines. Xylem sap, leaf tissue, and root tissue were collected at regular intervals during two seasons in conjunction with measurements of leaf water potential (Ψleaf) and stomatal conductance (gs). The different irrigation levels significantly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
75
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 43 publications
12
75
1
1
Order By: Relevance
“…On the one hand, ABA accumulation in the xylem sap of intact grapevine plants was highly dependent on the genotype, suggesting that ABA biosynthesis capacity or catabolism varied across genotypes. These variations may be due to differential expression of genes associated with ABA synthesis, such as NCED1 and NCED2, or genes coding for enzymes involved in ABA degradation to inactive compounds, including the ABA 8'-hydroxylases (Riahi et al, 2013;Speirs et al, 2013). On the other hand, exogenous ABA application to detached leaves using a high concentration (32 mmol m 23 (+)-ABA) reduced K leaf by up to 50% for the most sensitive grapevine genotype (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, ABA accumulation in the xylem sap of intact grapevine plants was highly dependent on the genotype, suggesting that ABA biosynthesis capacity or catabolism varied across genotypes. These variations may be due to differential expression of genes associated with ABA synthesis, such as NCED1 and NCED2, or genes coding for enzymes involved in ABA degradation to inactive compounds, including the ABA 8'-hydroxylases (Riahi et al, 2013;Speirs et al, 2013). On the other hand, exogenous ABA application to detached leaves using a high concentration (32 mmol m 23 (+)-ABA) reduced K leaf by up to 50% for the most sensitive grapevine genotype (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds were identified by retention times and multiple reaction monitoring. Parent and product ions were the same as previously described (Speirs et al, 2013).…”
Section: Aba Sampling In the Phenotyping Platform And Quantificationmentioning
confidence: 99%
“…For example, ABA-sensitive genes in guard cells both cause variation in leaf water potential through stomatal regulation and respond directly to water potential (e.g. Tardieu and Davies, 1992;Speirs et al, 2013). Therefore, inference regarding leaf water potential as a predictor should be interpreted carefully, possibly corroborated with comparisons among treatments.…”
Section: Discussion Of Best Practices In Field-scale Physiological Gementioning
confidence: 99%
“…In grapevine, the importance of ABA synthesis in roots in response to decreasing Ψsoil was recently shown by Speirs et al (2013). They reported that the expression of ABA biosynthetic genes NCED1 and NCED2 was higher in the roots than in the leaves upon drought and highest in the roots in months when soil moisture declined, vapor pressure deficit (VPD) was at its highest and stomatal conductance was impaired.…”
Section: Root Response To Drought: Aba Synthesismentioning
confidence: 98%